2009
DOI: 10.1038/jhg.2009.122
|View full text |Cite
|
Sign up to set email alerts
|

Association between ESR1 and ESR2 gene polymorphisms and hyperlipidemia in Chinese Han postmenopausal women

Abstract: Estrogen was considered to be an important protective factor for cardiovascular diseases in women. Genetic association studies suggested that variations of ESR1 and ESR2 genes might have a potential role in lipid profile. Our study aimed to investigate the association of single-nucleotide polymorphisms (SNPs) of ESR1 and ESR2 with hyperlipidemia in Chinese Han postmenopausal women. A total of 443 postmenopausal women aged between 55 and 71 years were recruited from Shanghai, China for a casecontrol study (154 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
(51 reference statements)
1
13
0
1
Order By: Relevance
“…A few association studies between ESR1 and ESR2 gene polymorphisms and lipid levels in response to HT have been published previously [13,20,22,24]. However, to the best of our knowledge, no study has investigated this particular SNP set for HT-dependent effects on lipid levels in postmenopausal women.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…A few association studies between ESR1 and ESR2 gene polymorphisms and lipid levels in response to HT have been published previously [13,20,22,24]. However, to the best of our knowledge, no study has investigated this particular SNP set for HT-dependent effects on lipid levels in postmenopausal women.…”
Section: Discussionmentioning
confidence: 90%
“…Silvestri et al [26] detected an association between the *G allele of rs4986938 and lower T-chol in HT+ postmenopausal women, while Saltiki et al [27] identified a link between the *A allele of rs4986938 and enhanced CVD risk in postmenopausal women. Zhao et al [22] and Almeida et al [24] did not observe an association of the rs4986938 polymorphism with a specific lipid profile.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations